Stability of Phenols, Antioxidant Capacity and Grain Yield of Six Rice Genotypes - Juthathip Kunnam; Wanwipa Pinta; Ruttanachira Ruttanaprasert; Darika Bunphan; Thanasin Thabthimtho; Chorkaew Aninbon (My University, 2023)
The environment is the main factor affecting variations in phytochemicals and antioxidant activity in rice. The objective of this study was to evaluate the stability of grain yield, phytochemicals and antioxidant capacity of six rice genotypes. Six rice genotypes were evaluated in a randomized complete block design with three replicates at three locations in Trat, Bangkok and Sakon Nakhon provinces in July-October 2019. Data on grain yield, yield components, total phenolic content, ferulic acid and antioxidant capacity were recorded. Grain yield was highest for crops grown in Bangkok, whereas antioxidant activity was highest for crops grown in Bangkok and Sakon Nakhon. Hom Nang Nual 1 and Mali Nil Boran had the highest grain yield. Riceberry had the highest grain yield in Trat; it also had high levels of total phenolic compounds, ferulic acid and antioxidant activity. Mali Nil Boran, Mali Nil Surin and Riceberry had the most stable total phenolic content, ferulic acid and antioxidant activity, respectively. Information on the levels and variability of phytochemicals in rice enables the selection of genotypes with high and stabile phytochemicals for production and rice breeding.
Keywords: GABA and Rice Research